The significant impact of the economic sustainability on the cement industry by the assessment of the key performance indicators using Taguchi signal to noise ratio. Issue 1 (1st January 2020) - Nawaz, Rashid; Hussain, Iftikhar; Noor, Sahar; Habib, Tufail; Omair, Muhammad
Abstract: The cement industry is one of the basic mineral-based industries that need strategic and operational sustainable development based on social, economic, and environmental indicators. The government's major infrastructural projects together with the China Pakistan Economic Corridor (CPEC) is one of the factors that motivate numerous local producers to aggressively install new plants and increase the capacity of existing plants. According to all Pakistan Cement Manufacturers Association (APCMA), there are 24 cement plants within the country producing approximately 47 million tons of cement per annum and many are planning to increase their capacities. The aim of this paper is to identify and rank the economic key performance indicators (KPIs) that have a significant impact on the economic sustainability of cement industries in Pakistan, using Taguchi signal to noise ratio (S/N). This study is based on survey perceptions held by the experts in the cement industry. 14 KPIs identified through literature review are discussed. The ranking provides an insight into what the industry experts regard as important KPIs and how they can be used to achieve economic sustainability. Increase in market share, new export markets, and operating cost per ton of cement production are considered to be the most important KPIs whereas investment in community, carbon credits, and tax reliefs from the government are considered to be the least important KPIs for economic sustainability of cement industry. Based on the results, it has been determined that increase in market share (i.e. Ec-2) is the most important KPI for economic sustainability and is followed by new markets explored for exports (i.e. Ec-5) and operating cost per ton of cement production (i, e.Ec-7) having scores of 28.6693 and 28.4952 respectively. Similarly, the Ec-14 representing "value of tax credits and tax reliefs received from government" is ranked the lowest with a score of 10.441.